Pengaruh Liberalisasi Keuangan terhadap Volatilitas Makroekonomi di Kawasan Asia-Pasifik - Feriansyah, Feriansyah; Achsani, Noer Azham; Irawan, Tony (UI Scholars Hub, 2018)
This paper examines the effect of financial liberalization on growth volatility of macroeconomics variable using dynamic panel model for nineteen Asia-Pacific countries for period of 1976–2015. Our results showed that the benefit of financial liberalization in Asia-Pacific region caused by the low volatility of the macroeconomic growth only occur in the group of developed countries, and not occur in the group of developing countries. This proved that the existence of financial liberalization provides no full beneficial effects in Asia-Pacific region.